Employment Trends of Master of Science in Home Economics Graduates from a State University in the Philippines (Journal of Pharmaceutical Negative Results, 2022)
Descriptive research to determine the employment trends of the Master of Science in Home Economics (MSIE) graduates. Thirty-four MSHE graduates of class 2017 to 2021 participated in the study by answering an online questionnaire during the first semester of the academic year 2021-2022. Interviews are also used as an alternative to gathering information. The profiling focused on MSHE graduates' identified variables. Findings showed that most MSHE graduates are permanent government teachers in junior high school and tertiary institutions and have either been promoted or transferred to a rank/position with tenure and higher level. Ten or 29.41% of MSHE graduates have been designated to various positions according to their skills and leadership potential. The top five helpful knowledge and skills were planning and organisation, use of technology, creativity, technical skills, soft skills, and communication.